Exaggerate (Zeyadah) and its Impact in the Worship Comparative Study of Fiqh Between the Four Madzhab - Khadafi, Muammar; , Dr.Muindinillah Basri, M.A (2013)
This research (thesis) is submitted by the student Muammar Khadafi under the supervision of Dr. Mu`inudinillah Bashri and DR. Taufik Qulazhar Hulaimi to obtain Master's degree In the Department of (Islamic Jurisprudence and Assets). The law of God to us through in the Holy Quran and the hadith of the Prophet peace be upon Him the various kinds of worships such as purity, prayer, zakat, fasting and pilgrimage (hajj), etc. subsequently, arose the various opinion of people in understanding the statetement of Prophet peace be upon Him on how to perform such worship. Some of them may increased a predetermined number or the capacity of worship , in the contrary, there were also who reduced the decided number by the way they are based on a reason or other. This research will analyze deeply about the provision related to the exaggerate (Zeyadah) in five chapters of Jurisprudence as follow : Purity and prayer, zakat, fasting, and pilgrimage. Hereinafter, it is written through inductive approach followed by accumulating the related writing and statement of the Scholars in this subject. Also the order of them and reason, afterward an explanation of the correct statement. Finally it will be attached also by the deductive approach to solve any kinds of such mentioned issue. It is expected from this research to inform the reader that the provision related to Zeyadah is different for the various issues, as it may be legitimated, and may be prohibited, and it has been conducted by the five provision namely : obligatory (wajeeb), mandub, outlawed (mahdzoor), hated (makrooh), and permissible (mobah).